Do loans for higher education lead to better salaries? evidence from a regression discontinuity approach for Colombia (2014)
Since 2002 the ACCES credit for higher education has financed more than 280,000 students. Prior evaluations have shown evidence as to its positive effect on the academic performance and the reduction in the dropout rates of the recipients. Nevertheless, no evidence exists so far on the effect these credit programs have had on the labor market indicators of their beneficiaries. In this study we attempt to estimate such effect. In particular, the question we seek to answer is if, once working as graduates, do the beneficiaries of ACCES loans have higher salaries and if this is the case, why does this happen and through which channels does it occur. Using administrative data for more than 300 thousand applicants of this credit in Colombia and using a regression discontinuity design, we found that the recipients of the ACCES educational credit have starting salaries as graduates which are higher in comparison with those graduates not receiving this credit. We also undertake a mediation methodology within an Intent-to-Treat Regression Discontinuity framework that allows for a precise identification and quantification of the mediation channels. We concluded that once graduated, the ACCES beneficiaries' exhibit longer job search periods, which would substantially explain their greater starting salaries of their first formal jobs. Academic performance during college also account for the differences in starting salaries yet to lesser degree.